Alternative tool to engage learners in comprehending written forms in mandarin - Kumaran, Arutchelvi K.; Chong, Geeng Ling; Vasuthavan, Evelyn Sharminnie; Vijayarajoo, Angeline Ranjethamoney; Teoh, Joo Tong (UiTM Cawangan Johor, 2021)
In the Malaysian content, Mandarin is taught as a foreign language. Learning the written forms can be challenging, especially for non-native speakers. Furthermore, teachers found this component to be problematic, based on learners' classroom written tasks. In order to assist learners' comprehension of the written form, a board game called 'Catch MelfYou Can' was developed. The focus oft his study is to find out the effectiveness of the board game in learning the written forms. The study sample consisted of20 respondents from a local University. Data comprised the responses from questionnaires and inten1iews. A pre and post test was administered to gauge students' performance in the written tasks. The findings showed the respondents enjoyed learning the written forms in a fun and engaging way. Hence, this game can be used as complementary tool in the teaching and learning of written forms.